Modification of a conventional photolytic converter for improving aircraft measurements of NO2 via chemiluminescence - Nussbaumer, Clara M.; Parchatka, Uwe; Tadić, Ivan; Bohn, Birger; Marno, Daniel; Martinez, Monica; Rohloff, Roland; Harder, Hartwig; Kluge, Flora; Pfeilsticker, Klaus; Obersteiner, Florian; Zöger, Martin; et al. (Atmospheric measurement techniques, 2021)
Abstract. Nitrogen oxides (NOx≡NO+NO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="85pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="2f82bf52594ce7ed0138de6f6b27db69"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-14-6759-2021-ie00001.svg" width="85pt" height="13pt" src="amt-14-6759-2021-ie00001.png"/></svg:svg>) are centrally involved in the photochemical processes taking place in the Earth's atmosphere. Measurements of NO2, particularly in remote areas where concentrations are of the order of parts per trillion by volume (pptv), are still a challenge and subject to extensive research. In this study, we present NO2 measurements via photolysis-chemiluminescence during the research aircraft campaign CAFE Africa (Chemistry of the Atmosphere - Field Experiment in Africa) 2018 around Cabo Verde and the results of laboratory experiments to characterize the photolytic converter used. We find the NO2 reservoir species MPN (methyl peroxy nitrate) to produce the only relevant thermal interference in the converter under the operating conditions during CAFE Africa. We identify a memory effect within the conventional photolytic converter (type 1) associated with high NO concentrations and rapidly changing water vapor concentrations, accompanying changes in altitude during aircraft measurements, which is due to the porous structure of the converter material. As a result, NO2 artifacts, which are amplified by low conversion efficiencies, and a varying instrumental background adversely affect the NO2 measurements. We test and characterize an alternative photolytic converter (type 2) made from quartz glass, which improves the reliability of NO2 measurements in laboratory and field studies.